The Relic of Our Distant Past: Prospects for Ex-Ante Emergency Laws Reform in Indonesia - Bimo Fajar Hantoro (Jurnal Kajian Pembaruan Hukum, 2026)
The 1945 Constitution establishes two mechanisms for dealing with emergencies, including Article 12, which requires the enactment of an ex-ante law governing the state of emergency. However, a dualism has emerged within Indonesia’s ex-ante emergency laws. The purpose of this research is to analyse the current regulatory landscape of ex-ante emergency laws, assess their constitutionality and limitations, and propose a constitutional framework for the law on the state of emergency, followed by reform proposals based on best practices. This normative legal research employs statutory and conceptual approaches, utilising primary and secondary legal materials. The findings show that there has been a “balkanisation” of ex-ante emergency laws, as evidenced by the existence of: 1) the law on the state of emergency model, which implements the delegation provision of Article 12; and 2) the ordinary legislation model, which deviates from the constitutional requirement of Article 12. To ensure compliance and harmonisation with Article 12, the various types of emergencies, which are currently dispersed across several laws, must be consolidated into a single law on the state of emergency. This unification should be followed by reforms to the regulations governing declaration authority, conditions for declaration, and the consequences of the state of emergency. These measures are necessary to ensure that the President is well-equipped to deal with emergencies while maintaining effective checks to prevent the abuse of presidential emergency powers